Haricen satış - Keçeci, Tuğba (My University, 2009)
Bu çalışmanın konusunu haricen satış oluşturmaktadır. Bu kapsamda genel olarak sözleşmelerde şekli, taşınmaz satım sözleşmesi, unsurları, taşınmaz alım satımı için verilen vekaletin şekli, tapusuz taşınmazların satımı ile resmi şekle uygun yapılmamış taşınmaz satım sözleşmesinin geçersizliği, şekil şartı dışındaki diğer geçersizlik sebepleri ve halleri inceleme konusu yapılmıştır. MK.m.706 ve BK.m.213 ’te taşınmaz mülkiyetini devretmeyi amaçlayan sözleşmeler şekil şartına tabi tutulmuştur. Burada resmi şekilden amaç akdin resmi görevli tarafından resen düzenlenmesidir. Resmi şekil şartına uyulmadan yapılan taşınmaz satım sözleşmesi geçersizdir. Ancak her durumda geçersizlik müeyyidesinin uygulanması MK.m.2 uyarınca adalet duygularını ağır derecede zarar verebilir. İşte bu gibi durumlarda tarafların edimlerini ifa edip etmemeleri de dikkate alınarak özel hallerin varlığı halinde akde geçerlilik sağlamak mümkündür. Bu doğrultuda haricen satış sözleşmesine hakkın kötüye kullanılması yasağı, Venire Contra Factum Propium ilkeleri ve Culpa in Contrahendo ile geçerlilik kazandırılmasının mümkün olup olmadığı tartışılmış bu konudaki doktrindeki görüş ayrılıkları ile yargı kararları incelenmiştir. Akde geçerlilik kazandırılamadığı hallerde ise alıcının talep çeşitleri araştırılmış ve sebepsiz zenginleşmeye dayalı alacak yada BK.m.41/ 2 uyarınca tazminat talep etme hakları yargı kararları ile birlikte incelenerek çalışmamıza son verilmiştir.

This study constitues the subject of externally sales. In this context, generally in contracts; formal, immovable selling contract, their components,the configuration of the power of attorney for immovable purchasing and selling, selling of immovables without title and the invalidity of immovable selling contract that hasn’t been made appropriate for the official form, other invalidity reasons and conditions accept from provision form has been made investigation subject. In Article 706 of New Civil Code and in Article 213 of Code of Obligations, the contracts aiming to transfer the possesion of the immovable property are subject to condition of official form. The official form here means that the contract is independedly prepared by formal officer. The sale contract of immovable property not conforming the official form is invalid. However performing the invalidity sanction in every situation maydamage the judgement seriously according to the Article 2 of Civil Code. Thus in these kind of special situations, the contract may be accepted as valid bay giving attention whether the parties the parties fulfil the conditions of the contract. In this direction, the ban of using the right badly to extarnaly sales contract,with Venire Contra Factum Promium principals and Culpa in Contrahendo , it has been discussed wheather it is possible to entitle the lagality, conception differences and ruling judgements on this case in the doctrine have been investigated. In the case of which the contract is not entitled legaly the demonial varieties of the purchaser have been researched and because of the not reasonable enrichment money on account or according to Article 41/ 2 of Code of Obligations the right of asking for indemnity has been investigated with the ruling judgements and our study has been put an end..
Keywords: Hukuk; Özel Hukuk